TOWARD A NEW COMPLICITY FOR NEW MEDIA. - Mandel, Naomi (Comparative Literature Studies, 2019)
This essay defines the field of thought on complicity, agency, and ethics from its formative moment after World War II to the early twenty-first century, and describes how the field must evolve in light of the ethical and political implications of mass digitization, social networking, and Web 2.0.